Characteristics of primary Sjögren's syndrome patients with IgG4 positive plasma cells infiltration in the labial salivary glands. Issue 1 (January 2017) - Liu, Chang; Zhang, Huayong; Yao, Genhong; Hu, Yunxia; Qi, Jingjing; Wang, Yan; Chen, Weiwei; Tang, Xiaojun; Li, Wenchao; Lu, Liwei; Gu, Luo; Sun, Lingyun
Abstract The purpose of this study was to investigate the characteristics of primary Sjögren's syndrome (pSS) patients with IgG4 positive (IgG4+ ) plasma cell infiltration in labial salivary glands (LSGs). Paraffin sections of LSGs from 336 pSS patients were stained with IgG4 and IgG monoclonal antibodies. According to the infiltration of IgG4+ plasma cells, patients were divided and clinical and serological characteristics were analyzed and compared. Based on the infiltration of IgG4+ plasma cells in the LSGs, patients were divided into three subgroups, low IgG4, moderate IgG4, and high IgG4 groups. A negative association between the number of infiltrated IgG4+ plasma cells and the disease characteristics was observed. We found that the higher the IgG4+ expression in plasma cells, the lower the positive rates of serum anti-SSA antibodies, anti-SSB antibodies, antinuclear antibodies (ANA), and rheumatoid factor (RF). Besides, patients from the high IgG4 group had the highest frequency of interstitial lung disease (ILD, 30.6%) and tubulointerstitial nephritis (TIN, 13.9%), but the lowest frequency of leucopenia (13.9%), thrombocytopenia (11.1%), and abnormal thyroidal function (0%). PSS patients with different IgG4+ plasma cells infiltration in the LSGs had distinctive clinical and laboratory characteristics. It may help us to further understand the role of IgG4+ plasma cells in pSS.